Prototype Perancangan Sistem Otomatis Penutup Jendela Kaca dan Penggerak Wiper Pada Mobil Berbasis Arduino Uno R3 - Asrul Asrul; Sudirman Sahidin; Danial Arista (Jutkel: Jurnal Telekomunikasi, Kendali dan Listrik, 2020)
To make it easier for motorists to use wipers automatically, a design is made, that is, a design is made, namely "AUTOMATIC PROTOTYPE DESIGN OF GLASS WINDOW CLOSING AND WIPER MOVING IN ARDUINO UNO R3 BASED CAR." The working method of this system is when the rain sensor detects the presence of water, this sensor will send analog data to Arduino. The data will be processed by Arduino provided that if the sensor is not given water, the value that is read at a level above 600 then the condition of the wipper motor does not rotate. When the sensor is given a little water until the sensor gets wet, the readable value tends to decrease and when it reaches the value of 600 under the condition of relay 1 HIGH and relay 2 LOW which causes the wipper motor to spin slowly. If the sensor continues to be given water so that the sensor becomes very wet, the value read on the sensor will continue to decrease and when it reaches a value below 400 then relay 1 LOW and relay 2 HIGH which causes the motor to spin rapidly.